Dissecting Flavivirus Biology in Salivary Gland Cultures from Fed and Unfed Ixodes scapularis (Black-Legged Tick) - Jeffrey M. Grabowski (American Society for Microbiology, 2019)
ABSTRACT The Ixodes scapularis tick transmits a number of pathogens, including tick-borne flaviviruses (TBFVs). In the United States, confirmed human infections with the Powassan virus (POWV) TBFV have a fatality rate of ∼10% and are increasing in incidence. Tick salivary glands (SGs) serve as an organ barrier to TBFV transmission, and little is known regarding the location of TBFV infection in SGs from fed ticks. Previous studies showed I. scapularis vanin (VNN) involved with TBFV infection of I. scapularis ISE6 embryonic cells, suggesting a potential role for this gene. The overall goal of this study was to use SG cultures to compare data on TBFV biology in SGs from fully engorged, replete (fed) ticks and from unfed ticks. TBFV multiplication was higher in SGs from fed ticks than in those from unfed ticks. Virus-like particles were observed only in granular acini of SGs from unfed ticks. The location of TBFV infection of SGs from fed ticks was observed in cells lining lobular ducts and trachea but not observed in acini. Transcript knockdown of VNN decreased POWV multiplication in infected SG cultures from both fed and unfed ticks. This work was the first to identify localization of TBFV multiplication in SG cultures from a fed tick and a tick transcript important for POWV multiplication in the tick SG, an organ critical for TBFV transmission. This research exemplifies the use of SG cultures in deciphering TBFV biology in the tick and as a translational tool for screening and identifying potential tick genes as potential countermeasure targets. IMPORTANCE Tick-borne flaviviruses (TBFVs) are responsible for more than 15,000 human disease cases each year, and Powassan virus lineage 2 (POWV-L2) deer tick virus has been a reemerging threat in North America over the past 20 years. Rapid transmission of TBFVs in particular emphasizes the importance of preventing tick bites, the difficulty in developing countermeasures to prevent transmission, and the importance of understanding TBFV infection in tick salivary glands (SGs). Tick blood feeding is responsible for phenomenal physiological changes and is associated with changes in TBFV multiplication within the tick and in SGs. Using SG cultures from Ixodes scapularis female ticks, the primary aims of this study were to identify cellular localization of virus-like particles in acini of infected SGs from fed and unfed ticks, localization of TBFV infection in infected SGs from fed ticks, and a tick transcript (with associated metabolic function) involved in POWV-L2 infection in SG cultures.